Rompendo o silêncio: dimensões da experiência de professoras/es surdas/os na educação básica - Silva, Gracileide Alves da (2021)
The present work seeks to look at the experiences of deaf people in the teaching profession, contribute for their silencing not to be replicated. The study originated from the experiences and concerns of the teacher-researcher, when observing deaf teachers in challenging situations in schools self-designated as inclusive. Those concerns originated the present thesis research, whose overall goal is to analyze teaching experiences of deaf teachers in schools which are thought and planned for listeners. Specifically, it is intended to identify and reflect about the stressful situations inscribed in such experiences; narrate significant moments that reveal the charms and disappointments about being a deaf teacher in schools for listeners; and problematize the interactions of the deaf professionals in the school environment and how they see and feel the perceptions and points of view of students and other teachers and professionals in the school.This investigation was carried out in the Post-graduation Program in Education, linked to the Cultural Studies in Education research line, at the Federal University of Paraíba (UFPB), and is based on Deaf Studies, of Education and Deaf Studies, coupled with sociological discussions on condition / teaching work and teacher sociocultural individuals. The analytical material was produced from field observations and narrative interviews, conducted in four Basic Education schools in João Pessoa-PB; and involved six deaf teachers. The data collection period occurred from October to December 2019. This work developed the thesis that teaching experiences by deaf people, in so-called inclusive schools, are constituted by multiple tensions and lead to processes of stigmatization and inferiorization and cause, at the same time, the search for recognition. These are situations and contexts in which the deaf teachers are in the condition of excluded from within the school and subordinate inclusion, in the terms used by Pierre Bourdieu and Patrick Champagne (1998) and José de Souza Martins (2009), respectively.